Filter to Retrieve Studies Related to Indigenous Peoples of Newfoundland and Labrador in the OVID MEDLINE Database ... - Dorgan, Marlene; Campbell, Sandy; Tjosvold, Lisa (University of Alberta Library, 2013)
This is one of a suite of filters designed to retrieve studies related to Canadian Indigenous Peoples in the OVID MEDLINE database. This filter is specific to Newfoundland and Labrador. ...